Linking occupational therapy models and assessments to the ICF to enable standardized documentation of functioning. (October 2018) - Maritz, Roxanne; Baptiste, Sue; Darzins, Susan W.; Magasi, Susan; Weleschuk, Chelsey; Prodinger, Birgit
Background: The International Classification of Functioning, Disability and Health (ICF) can serve as reference for standardized documentation of health in clinical practice. Purpose: This study aims to bridge the gap between the ICF and occupational therapy specific concepts, represented by occupational therapy models and their derived assessments. Method: Occupational therapy assessments in relation to their models were systematically linked to the ICF, and a compatibility analysis was conducted. To strengthen reliability of the linkings, feedback from the respective assessment hosts was obtained. Findings: Linking tables were developed for the Assessment of Motor and Process Skills, the Canadian Occupational Performance Measure, and the Model of Human Occupation Screening Tool. Similarities and differences between the ICF and the three assessments and their associated models show how they differ from and complement each other. Implications: The findings of this study lay the foundation for standardized documentation in occupational therapy and enhance the practicability of the ICF.